Friction and wear properties of bushing bearing of graphite filled short glass fibre composites in dry sliding - Srivastava V.K.; Pathak J.P. (My University, 2025)
The paper discusses the effect of participate additions on the friction and wear of short glass fibre reinforced epoxy resin composites. Particles of graphite were mixed with the epoxy resin prior to composing with short glass fibre. Bushing samples were prepared with varying graphite contents and percentage of glass fibre. Tests were performed on bushing samples to obtain the friction and wear for the composites with varying applied load and sliding time. It was found that graphite has an important impact on the wear and friction properties of glass fibre reinforced epoxy resin composites. It is clear that after an incubation period, there is a nearly linear relationship between wear load and sliding time. Wear increases with load and time, but as the amount of graphite in the composite increases, its value decreases irrespective of the applied load and sliding time, due to increase of wear resistance in matrix materials. However, friction increases only with sliding time but decreases with the increase of graphite particles irrespective of time.